Three-dimensional characteristics of shrinkage porosities in Mg-xAl-1Zn-0.2Mn alloys and their relationship with microstructures - Chuangming Li; Ang Zhang; Yongfeng Li; Yuhong Cui; Zongliang Tan; Zhihua Dong; Guangsheng Huang; Bin Jiang; Fusheng Pan (Journal of Materials Research and Technology)
Shrinkage porosities are microscopic casting defects that significantly deteriorate material properties. This study examines the three-dimensional characteristics of shrinkage porosities in Mg-xAl-1Zn-0.2Mn (x = 3, 6, 9 wt%) alloys and explores the effects of Al content on these porosities, as well as their interaction with the alloy microstructures. Results show that the Al content influences the distribution, size, and morphology of shrinkage porosities by affecting dendritic coherency, secondary phases, and skeleton morphology during solidification. The volume of the shrinkage porosities is measured, and its variation is linked to uneven changes in the alloy's shrinkage and feeding characteristics. Additionally, the study analyzes the effect of casting pressure, based on casting height, on the types of shrinkage porosities. This study provides a detailed explanation of the microscopic formation mechanism of shrinkage porosities, aiming to offer theoretical foundation for reducing porosities.